Training on multiple days results in better learning in embedded eyeblink conditioning in young human adults - Winton, Robert; Pious, Meenam; Rasmussen, Anders ; 0000-0003-4477-369X (npj Science of Learning, 2025)
Eyeblink conditioning is mediated by similar cerebellar pathways in humans and animals and is typically investigated using delay or trace protocols. These studies show that humans can easily acquire eyeblink conditioning within a single day of training whereas animals usually require around 3-10 days of acquisition training before they consistently exhibit conditioned responses. We aimed to study how a multiple-day acquisition training, across 3 non-consecutive days of a month, with 100 trials per day affected learning in young human adults. We employed an embedded protocol in which the US is embedded within the CS duration without co-termination. Our findings show, for the first time in humans using this protocol, that learning improves substantially on days 2 and 3. Our findings encourage research into how human cerebellum mediates consolidation across several days of eyeblink conditioning as well as into the neurocognitive mechanisms of the relatively underexplored embedded eyeblink conditioning protocol.
© 2025. The Author(s).